2014
DOI: 10.1080/1539445x.2014.896822
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Interaction Between Bovine Serum Albumin and Terbium Complex Containing Polymer

Abstract: The interactions between bovine serum albumin (BSA) and polymer [poly(METAC-co-NIPAm-co-Tb(AA) 3 Phen·H 2 O), denoted as PMNTb] containing terbium has been investigated with fluorescence spectroscopy, zeta-potential and size measurements, and transmission electron microscopy (TEM). PMNTb was found to interact with BSA through the electrostatic interaction, and it quenches the fluorescence of BSA based on the static quenching mechanism. The distance between PMNTb and BSA was estimated to be 1.9 nm based on Föst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The quenching mechanism is generally classified as either dynamic or static. Higher temperatures would result in faster diffusion and dissociation of weakly bound complexes, leading to larger contribution from dynamic quenching and a lower contribution from static quenching . As shown in Table , the values of K SV are inversely correlated with temperature, which indicates that the quenching mechanism of LYSO fluorescence by CPS may not be initiated by dynamic collision, but by complex formation .…”
Section: Resultsmentioning
confidence: 89%
“…The quenching mechanism is generally classified as either dynamic or static. Higher temperatures would result in faster diffusion and dissociation of weakly bound complexes, leading to larger contribution from dynamic quenching and a lower contribution from static quenching . As shown in Table , the values of K SV are inversely correlated with temperature, which indicates that the quenching mechanism of LYSO fluorescence by CPS may not be initiated by dynamic collision, but by complex formation .…”
Section: Resultsmentioning
confidence: 89%
“…Besides, the results from the negative value of ∆G clarified that there had been a spontaneous reaction between PEP and CFP [15]. A negative ∆H and positive ∆S showed that the electrostatic interaction played a major role in the binding process [16]. The same conclusion of the three experimental methods indicated that when researched the type of interaction between drugs and proteins, the resonance light scattering method, ultraviolet absorption method and the traditional fluorescence quenching method were both feasible.…”
Section: Type Of Interaction Force Of Pep-cfp Systemmentioning
confidence: 82%